A retrospective study on the carbon footprint of bodies donated to science for sustainable medical education and research - Barausse, Carlo; Tayeb, Subhi; Bonifazi, Lorenzo; Lodi, Simone; Mariani, Giulia Adalgisa; Orsini, Ester; Zanni, Sara; Bonoli, Alessandra; Manzoli, Lucia; Ratti, Stefano (Frontiers in Medicine, 2025)
IntroductionA comprehensive understanding of human anatomy is essential for medical education, with donated human body dissection remaining the gold standard for this purpose. However, in countries where there is a shortage of locally donated bodies, anatomical centers are increasingly turning to external body donation programs, such as those in the United States, to meet their needs.MethodsThis study assesses the carbon footprint (CO2e) of locally sourced vs. internationally sourced donated bodies, with the carbon footprint of the latter being estimated hypothetically. A retrospective observational study using Life Cycle Assessment (LCA) methodology was conducted to evaluate the environmental impacts. The analysis included factors such as transportation, preservation methods (fresh vs. embalmed), and additional aspects such as refrigeration and aeration.ResultsLocally donated bodies had an average transport distance of 201.19 ± 172.78 km, resulting in 14 ± 11.84 kgCO2e per body. In contrast, international transport from the US hypothetically produced approximately 450.375 kgCO2e per body, representing a 3114.3% increase. The total carbon footprint for a locally donated body was 8948.99 kgCO2e annually. These findings suggest that local donation programs could significantly reduce transportation emissions, making them more eco-friendly.DiscussionPromoting local donation programs could not only enhance educational opportunities but also minimize the environmental impact of anatomical studies. Increasing the number of local donors would optimize the use of management systems, such as aeration and refrigeration, further improving sustainability. Due to the limitations of this study, further research is needed to refine these findings and explore strategies for reducing the carbon footprint in medical training.